Performance of Tropical Pine Under Different Silvoclimatic Zones of Tamil Nadu - Bari, P. A. Abdul; Prasad, K. G. (Indian Forester, 1989)
Field trials of P. caribaea and P. oocarpa were undertaken from 1979 onwards under different Silvoclimatic zones in Tamil Nadu. Performance of P. caribaea and P. oocarpa are evaluated in relation to soil properties of each zone and comparative study is discussed in this paper, after analysing the data statistically.